Endodontic diagnosis: evaluation between clinical and histological findings - Paloma Souza Gonçalves; Sílvio Albergaria; Lilian Dantas de Góes Silva; Jean Nunes dos Santos (Faculdade São Leopoldo Mandic, 2008)
Objective: In this study, the aim was to analyze the histologic alterations in thirty dental pulps and correlate them with the clinical findings to verify agreement between the clinical and histopathologic diagnosis and contribute to knowledge about endodontic diagnosis. Methods: Using the methodology of Oliveira4, the pulpal conditions were clinically classified as normal, reversible pulpitis, pulpitis at the stage of transition, irreversible pulpitis and necrosis. Results: Lack of correlation was observed between the clinical and histopathologic diagnoses in the cases classified as reversible and at the stage of transition, which histologically consisted of irreversible lesions or degenerative alterations. All the cases clinically classified as irreversible corresponded to the histologic diagnoses. Conclusion: It was concluded that the correlation between clinical and histopathologic diagnosis of dental pulp was shown to be controversial, even though the semiotechnique used had been imperative for guidance about the irreversibility of pulpal lesion.